Against a hierarchy of expressive means; arguments for new pedagogies in performer education in India and the UK. Issue 2 (4th May 2019) - Ananthakrishnan, B.; Collins, Jane
Abstract: This article reflects on the findings of an intercultural, transdisciplinary workshop, which engaged drawing, performance and digital technology, conducted at the University of Hyderabad, India, in 2014, with theatre and fine art students from Sarojini Naidu School of Arts and Communication, Hyderabad and Wimbledon College of Arts, London. We argue for the value of this kind of practical experiment, where students worked alongside each other on a project from the same starting point, in terms of what it revealed about the hierarchical assumptions embedded in the fields of theatre and fine art, in India and in the UK. These hierarchies are being challenged by digital technologies and we call for new pedagogies in the arts to address this. In this reflection on the outcomes of the project, we focus primarily on performer training and align our findings with music theatre director/composer Heiner Goebbels' arguments against a hierarchy of 'expressive means' in performance. We conclude by advocating more programmes in universities and academies, both in India and the UK, where performers, sound and visual artists, designers, digital artists and makers can work not only in more integrated ways but also alongside each other.